The Effect of Training and Decent Work on Employee Performance with Motivation as Mediation at PTPN IV KSO Reg. II Kebun Tanjung Garbus - Anum, Putri Latifah; Shafira, Shalsabilla; Fitriyanti, Mira; Dalimunthe, Ritha F. (Westscience Press, 2024)
This study aims to examine the effect of training and decent work on employee performance with motivation as a mediating variable at PTPN IV KSO Reg. II Tanjung Garbus Gardens. This research is included in quantitative research, the population is employees of PTPN IV KSO Reg. II Kebun Tanjung Garbus totaling 341 employees and the method of determining the sample using non probability sampling, namely permanent employees at PTPN IV KSO Reg. II Kebun Tanjung Garbus which is determined using the slovin formula, so the sample amounted to 184 employees. The data analysis method used SEM PLS and the data collection method used a questionnaire. The results of this study found that training has no effect on employee performance, decent work has a positive and significant effect on employee performance, training has a positive and significant effect on motivation, decent work has a positive and significant effect on motivation, motivation has a positive and significant effect on employee performance, training has a positive and significant effect on employee performance through motivation and decent work has a positive and significant effect on employee performance through motivation.